The Material Situation of Polish Workers Between 1945 and 1956 - Chumiński, Jędrzej (Studia Historiae Oeconomicae, 2014)
The article deals with the problem of the material situation of workers between 1945 and 1956. It was particularly difficult in the first months after the end of the war when “cheap labour’ was the immanent feature of so-called “real socialism”. The problem became even more severe due to the policy of “underconsumption” proclaimed in 1946 by one of the directors of the Central Planning Office and introduced as the basis of financing the investment plan. Keeping a disproportionately high level of accumulation at the expense of consumption was a prominent feature of the system.